2019
DOI: 10.3748/wjg.v25.i21.2650
|View full text |Cite
|
Sign up to set email alerts
|

Novel risk scoring system for prediction of pancreatic fistula after pancreaticoduodenectomy

Abstract: BACKGROUND The available prediction models for clinically relevant postoperative pancreatic fistula (CR-POPF) do not incorporate both preoperative and intraoperative variables. AIM To construct a new risk scoring system for CR-POPF that includes both preoperative and intraoperative factors. METHODS This was a retrospective study of patients who underwent pancreaticoduodenectomy (PD) or pylorus-preserving PD (PPPD) between January 2011 and Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 34 publications
0
19
0
9
Order By: Relevance
“…Previous studies analyzed risk factors for POPF and developed risk prediction tool using scoring system. 22,[36][37][38][39][40] However, few studies have built a nomogram based on individual risk factors. After our extensive review, only one study has tried to develop a nomogram for the prediction of POPF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies analyzed risk factors for POPF and developed risk prediction tool using scoring system. 22,[36][37][38][39][40] However, few studies have built a nomogram based on individual risk factors. After our extensive review, only one study has tried to develop a nomogram for the prediction of POPF.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the univariate analysis, the risk prediction model using BP-ANN involving 9 significant factors for predicting HAI occurrence among elderly PD patients was finally constructed. The overall prediction accuracy of the model, 93.79%, was obviously higher than the reported predictive rate of 75.7% conducted in lung cancer patients [32] and 82.49% conducted among hematological diseases patients [41], and also higher than the reported predictive performance conducted by 10-point Braga risk score among patients underwent PD [28]. It had indicated that BP neural network prediction accuracy could reach approximately 90% by scientifically determining risk indicators and constructing appropriate network models [42], which was well verified in this study.…”
Section: Discussionmentioning
confidence: 67%
“…Joliat GR et al applied the Braga score to calculate the overall risk score for the prediction of complications after PD [27]. A risk scoring system with 10-point based on logistic regression was also established to predict the pancreatic fistula [28]. However, most of studies mainly focused on general age groups, and just described one or more postoperative complications rather than targeting HAIs.…”
Section: Introductionmentioning
confidence: 99%
“…For most preoperative and intraoperative static indexes, our result shows that only a few of them could predict the occurrence of CR-POPF, apart from preoperative serum albumin and creatine levels. This is possibly due to the fact that there's still no strong consensus about the association between these factors and CR-POPF, which probably leads to the inconsistencies in the prediction models developed recently [9,10,16,18]. However, we noted that the patients who developed CR-POPF tend to have an advanced age [44,45], higher BMI [46,47], softer pancreas [48][49][50], and smaller pancreatic ducts [48,[51][52][53][54][55], were less likely to have diabetes [47,56], and were more likely to have had portal vein resection [57], which are comparable to findings of previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, postoperative drainage fluid amylase (DFA) and C-reactive protein-to-serum-albumin ratio (CAR) seemed to be the accurate and widely used indexes for the prediction of CR-POPF, especially in a particular time-point, in which they are suggested to be useful and critical predictive indexes [11][12][13][14]. However, preoperative and intraoperative factors indicating CR-POPF seemed to vary [15][16][17][18], furthermore, such prediction result cannot be updated according to the changes in the patient's fluctuating state and examination results over time.…”
mentioning
confidence: 99%